Role of diagnostic hystero-laparoscopy in the evaluation of female infertility - Shanmugham, Deepa; Sahitya, Nambala Divya; Natarajan, Sindhu; Saravanany, Deepak Kannan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Infertility affects about 10-15% of reproductive age couples. The main causes of infertility include male factor, ovulatory disorders, tubal factor and endometriosis. This study was conducted to determine the role of Diagnostic hystero-laparoscopy (DHL) in the evaluation of female infertility. Methods: This study was a prospective study done in a tertiary care centre over a period of 1 year on all infertile couples. The exclusion criteria: male factor infertility, hypothyroidism, hyperprolactinemia, acute pelvic inflammatory disease. Diagnostic hysterolaparoscopy was performed in all study patients in pre ovulatory phase, under general anaesthesia. The findings were then documented and analysed. Results: A total number of 90 patients were recruited for the study. The mean age of the patients was 28±3 years. The mean BMI of the study patients was 25±4 kg/m2. The mean duration of infertility was 5.4 years. On laparoscopy, 28 patients had polycystic ovaries (31.1%), 4 patients had pelvic adhesions (4.4%), 2 patients had endometriosis (2.2%) and tubal block was identified in 10 patients (11.11%). 10 patients had abnormal findings on hysteroscopy. Conclusions: Hystero laparoscopy is an effective diagnostic tool in the evaluation of infertility and has to be included in basic diagnostic workup.